Novel carbon polymorphs with cumulative double bonds in three-dimensional sp–sp2 hybrid framework. Issue 22 (26th April 2018) - Liu, Lingyu; Hu, Meng; Liu, Chao; Liang, Xiaowei; Pan, Yilong; Ying, Pan; Zhao, Zhisheng; Gao, Guoying; He, Julong; Tian, Yongjun
Abstract : Two new three-dimensional microporous carbon allotropes consisting of whorl chains connected by cumulative double bonds in a sp–sp 2 hybrid framework have been proposed in this study. Abstract : A conspicuous amount of theoretical study has been published on the properties of carbon allotropes with alternate single and triple bonds, (–CC–) n . However, theoretical characterizations of carbon allotropes with cumulative double bonds (CC) n is almost non-existent in literature. Based upon first-principles calculations, two new three-dimensional (3D) microporous carbon allotropes consisting of whorl chains connected by cumulative double bonds in a sp–sp 2 hybrid framework have been proposed in this study. One of these structures, namely, Trig-C9 was obtained by an evolutionary particle swarm structural search, while the other structure, denoted as Trig-C15, was obtained by inserting double bonds into Trig-C9 . Both the 3D sp–sp 2 hybridized carbons have a trigonal structure with 9 and 15 atoms in the hexagonal primitive cells. The calculated results demonstrate that these polymorphs are thermodynamically, mechanically, and dynamically feasible. Trig-C9 and Trig-C15 are indirect semiconductors with band gaps of 2.70 eV and 1.25 eV, respectively. Their unique frameworks render them mechanical ductility and significant elastic anisotropy. These results open up new horizons for the exploration of new carbon phases with unique structural, mechanical, and electronic properties.